Living Green: The Ultimate Teen Guide - Gay, Kathlyn (Rowman & Littlefield Publishers, 2012)
What does living green mean? For some, it means making a commitment to reduce, reuse, and recycle every day. For others, it also means respecting and conserving our natural resources, so they will be available in the future. In Living Green: The Ultimate Teen Guide, readers learn why protecting the environment is such a crucial undertaking and why and how young adults should take up this important cause. Living Green demonstrates how reckless indifference to our planet’s needs jeopardizes not only plants and animals but the existence of mankind. This volume addresses such concerns as leaving a low carbon footprint, protecting wildlife, saving natural resources, conserving trees and gardens, and fighting for environmental justice. Most importantly, Living Green explores the many ways that teens can make a difference—in their homes, communities, and in the world at large. While some of the teen efforts described here may be familiar, the author also focuses on issues seldom addressed, such as dumping toxic waste on poor and powerless communities. The book includes quotes from green advocates and teens who consider themselves eco-friendly, as well as useful advice that will help young adults embrace a lifestyle that will positively affect generations to come.